Effect of Edible Oils on Quality and Shelf Life of Low Fat Mayonnaise - Palma, A.; Aziz, M.G.; Chawdhury, M.M.; Uddin, M.B.; Alam, M. (Pakistan Journal of Nutrition, 2004)
The study deals with the effect of edible oils on quality and shelf life of mayonnaise. Three mayonnaise samples were prepared using palm oil, soybean oil and mustard oil at 30% (weight basis) level. Another sample of mayonnaise manufactured from olive oil was purchased from local market. In addition to lipid ingredients, egg (whole) and vinegar were used at 20% and 12% level respectively. The samples were analyzed for proximate composition. The moisture, protein, fat, ash, acidity and total solid content in 4 samples were found in the range of 41.94-46.95%, 1.09-1.62%, 30.29-33.40%, 1.15-1.80%, 0.48-0.82% and 18.65-23.72% respectively. A panel of 10 judges evaluated the sensory acceptability of the product. No significant difference in colour and texture was observed among the samples. However, samples containing soybean and palm oil had significantly higher acceptability compared to other samples.